Analisis Tingkat Kemacetan Lalu Lintas Dengan Memanfaatkan Citra Ikonos Dan SIG Di Ruas Jalan Letjend Suprapto,Jalan Ki Mangunsarkoro Dan Jalan Sumpah Pemuda Kota Surakarta - Alfandani, Rahardhiansyah Setiawan, Dra. Hj. Umrotun, M.Si (2016)
The Level of Traffic Congestion Research by using Ikonos satelite imagery and GIS in Jl. Letjend Suprapto, Ki Mangunsarkoro, and Sumpah Pemuda Surakarta in purpose: 1. to review the street service of Jl. Letjend Suprapto, Jl. Ki Mangunsarkoro, and Jl. Sumpah Pemuda Surakarta. 2. to reveal the characteristic of its traffic and the factors that causes congestion in Jl. Letjed Suprapto, Jl. Kimangunsarkoro, and Jl. Sumpah Pemuda. 3. to analyze the level of congestion in Jl. Letjend Suprapto, Jl. Kimangunsarkoro, and Jl. Sumpah Pemuda Surakarta. The method of the research is survey and the data are collected by calculating the amount of vehicles and the wide of the street. The method of collecting sample used in this study is purposive sampling which is taking into account of certain things. The samples are taken in the form of periodic daily number of vehicles. The calculation and observation of the service starts in office hour, at 06.00-08.00 named activities time, level of service in daytime peak at 12.00-14.00 named breaking times and school ends, in the afternoon peak at 16.00-18.00 named back to the activities and transformation from daytime to the night. There are three classes of Congestion Level, high class in range of 1,0 happens in Jl. Suprapto and Jl. Ki mangunsarkoro B, medium class in range of 0,8 happens in Jl. Sumpah Pemuda, low class in range 0,7 happens in Jl. Ki Mangunsarkoro A. The characteristic of the traffics which is used in this research is macroscopic research (flow, speed, density). Factors of the area which is affecting the congestion levels are land, the wide of the road, barriers and intersection.